Public health component in building information modeling; Journal of Physics: Conference Series; Vol. 1015 : Information Technologies in Business and Industry (ITBI2018) - Trufanov A. I.; Rossodivita A.; Tikhomirov A. A.; Berestneva O. G. Olga Grigorievna; Marukhina O. V. Olga Vladimirovna (Mathematical simulation and data processing, 2018)
Title screen